Islamic Financial Products/Services and the Intention to Use - Nelson Lajuni; Jati Kasuma; Yusman Yacob; Noor Hafizah Azali; Winnie Emang; Mohammad Bin Ismail (2020)
Muslims and non-Muslims alike have displayed a definite trend towards accepting Islamic financial products/services, thereby rendering it crucial to examine the determinants driving individuals to the intention to accept Islamic financial products/services. This study aimed to investigate the predictive power of Islamic financial literacy on the modified Theory of Planned Behaviour, which eventually translated into individual behaviour towards the intention to use Islamic financial products/services. Four hundred copies of questionnaires were distributed, out of which 300 usable copies were subsequently collected. The data obtained were then analysed using PLSSEM. The findings showed that all exogenous variables implemented, namely attitude, social value, perceived behavioural control, and Islamic financial literacy yielded explanatory and predictive power to predict individual intention to implement Islamic financial products/services. As financial services are humanised and localised to serve the customers better, this study extends the available literature by providing pertinent insights into the subject matter in the context of emerging markets.